2015
DOI: 10.1212/wnl.0000000000002225
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Impact of Symptoms in Myotonic Dystrophy Type 2 (PRISM-2)

Abstract: The lives of patients with DM2 are affected by a variety of symptoms. These symptoms have different levels of significance and prevalence in this population and vary across DM2 subgroups in different demographic categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 29 publications
5
57
1
Order By: Relevance
“…This investigation complements earlier work that addressed symptoms affecting other populations with neuromuscular disorders . As with those studies, we found that patients with longstanding and progressive neuromuscular disorders most frequently report difficulties with muscle weakness, fatigue, ambulation, the ability to perform specific activities, and emotional issues .…”
Section: Discussionsupporting
confidence: 84%
“…This investigation complements earlier work that addressed symptoms affecting other populations with neuromuscular disorders . As with those studies, we found that patients with longstanding and progressive neuromuscular disorders most frequently report difficulties with muscle weakness, fatigue, ambulation, the ability to perform specific activities, and emotional issues .…”
Section: Discussionsupporting
confidence: 84%
“…The Christopher Project study adds to prior smaller cross‐sectional studies that sought to define the level of DM disease burden from the patient's point of view . This study again provides evidence that symptoms and challenges are not only common and life‐altering, but also under‐recognized and under‐addressed in the clinical setting.…”
Section: Discussionmentioning
confidence: 85%
“…The study was also limited by relying on respondents’ accurate memory of historical facts about their diagnostic experience. Respondents also included patients who self‐reported having DM without confirmation through medical record review, in contrast to prior studies that required vetting of medical records . Regardless, this study again provides evidence that select groups with DM are capable of filling out a self‐report on the occurrence and relative importance of their clinical symptoms …”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations